Cancer vaccines inducing antibody production: more pros than cons. (September 2011) - Jensen-Jarolim, Erika; Singer, Josef
To date, passive immunotherapy with monoclonal antibodies is a well-established option in clinical oncology. By contrast, anticancer vaccines are less advanced, with the exception of successfully applied prophylactic vaccines against oncogenic virus infections. The creation of therapeutic vaccines is still a great challenge mostly due to the self-nature of tumor antigens. Therapeutic vaccines may be based on patient-specific material including pulsed effector cells, or tumor-associated antigens and derivatives thereof, such as peptides, mimotopes and nucleic acids. The latter represents a more universal approach, which would set an ideal economic framework resulting in broad patient access. In this article we focus on cancer vaccines for antibody production, in particular mimotope vaccines. The collected evidence suggests that they will open up new treatment options in minimal residual disease and early stage disease.